EXPLORATION OF MANGROVE ECOSYSTEM AMONG TEACHER TRAINEES THROUGH INQUIRY - Norazizah Abdul Rahman; Noor Ashikin Mohd Yusop; Ilyana Afiera Mohd Azaman (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2021)
This study aims to explore the 5E elements mastered by trainee teachers in the exploration of mangrove swamp ecosystem through inquiry method in Mangrove Forest, Johor. The research participants of this qualitative case study was involved two teacher trainees from Institute of Teacher Education Technical Education Campus Study. The research data were obtained through observations, documents and unstructured interviews. The findings showed  that trainee teachers have high curiosity, acquire 'big ideas' on the issues studied, able to solve problems, build new ideas that are more diversified and structured. Meanwhile, build and apply new science concepts in new situations. The results of the evaluation of drawings, writing and peers showed that the level of knowledge of trainee teachers increased after the process of exploration. In conclusion, this study may serve a guide in exploration activities at real field sites through inquiry-based learning for enhance scientific knowledge and concepts towards the growth of environmentally-smart citizen.